Beyond the storms: Exploring predictors of posttraumatic stress and posttraumatic growth among survivors of hurricanes Irma and Maria in Puerto Rico - Marie-Claire Meadows; Noelle Serino; Dahianira M. Camacho-Monclova; Kaumudi Joshipura; Sarah R. Lowe (The Journal of Climate Change and Health)
Background: Within disaster-affected communities, residents’ exposures and post-disaster mental health outcomes can vary widely. Yet, few studies have explored the relationship between such diverse disaster-related exposures and posttraumatic growth (PTG) in a Puerto Rican context. Methods: To address this gap, we used data from the Preparedness to Reduce Exposures and Diseases Post-hurricanes and Augment Resilience (PREPARE) study, a cohort of mainly Hispanic Puerto Ricans who experienced Hurricanes Maria and Irma in 2017. This analysis focused on 484 individuals who completed structured interviews 20 to 34 months after the hurricanes. We evaluated the associations between five different disaster exposures (e.g., financial, home damage, personal health, and familial health), posttraumatic stress (PTS), and PTG and its five domains (personal strength, new possibilities, improved relationships, spiritual growth, and appreciation of life), controlling for demographic, geographic, and social factors. Results: In multivariable models, higher total disaster score was associated with higher levels of both PTS and PTG (2.91 and 3.87, respectively). Personal health impacts were consistently associated with higher levels on all PTG subscales, ranging from 0.89 to 1.94, which was not the case for other exposures. Specifically, home damage was associated with higher levels on all PTG subscales except spiritual growth, and financial and familial health impacts were associated with greater identification with new possibilities and appreciation of life only. Conclusion: These findings provide novel evidence that different disaster-related exposures have distinct associations with the different PTG domains in Puerto Rico. These findings can inform future efforts to address post-disaster mental health ailments by bolstering different aspects of PTG.